This model world : travels to the edge of contemporary art - Byrt, Anthony (Auckland University Press, 2016)
In April 2011, Anthony Byrt was living in Berlin and building a career as a critic, writing about the world of contemporary art for magazines like Frieze and Artforum International. Then one day his world turned upside down. A baby boy, two weeks in intensive care, and Byrt, his wife and new-born son suddenly found themselves booked on a one-way trip home to New Zealand. 'This model world' is a portrait of what Byrt found when he came back. Built around hundreds of hours spent in galleries, artists' studios and on the road from Brisbane to Detroit to Venice, this is a deeply personal journey into the contemporary New Zealand art world and the global world it inhabits. It's a book about major figures like Yvonne Todd, Shane Cotton, Billy Apple, Peter Robinson, Judy Millar and Simon Denny, and emerging artists such as Luke Willis Thompson, Shannon Te Ao and Ruth Buchanan. It's about severed heads and failed cities; about bright young stars and old men with a final point to prove; about looking for God and finding Edward Snowden; and about what it means to investigate the boundary where our bodies hit the world. 'This model world, ' a riveting first-person account of one author's travels to the edge of contemporary art.